Exploring the role of macrophages in the progression from atypical hyperplasia to endometrial carcinoma through single-cell transcriptomics and bulk transcriptomics analysis - Song, Xiaolei; Na, Re; Peng, Nianghai; Cao, Wenming; Ke, Yan (Frontiers in Endocrinology, 2023)
In this study, we conducted single-cell analysis of macrophages in endometrial cancer to identify key genes. By combining the differentially expressed genes from bulk-seq of atypical endometrial hyperplasia and endometrial cancer, we determined the key genes and used TCGA tumor data to perform cluster analysis, which identified two different subtypes. We found that subtype B was closely related to cellular metabolism. Further analysis using LASSO regression identified a diagnostic model based on CDH18, H19, PAGE2B, PXDN, and THRB. Our model could effectively distinguish the prognosis of cervical cancer. Based on these three key genes, we constructed a prognosis model and a column chart. Finally, through CIBERSORT analysis, we found that CDH18 and PAGE2B were strongly associated with macrophage M0. We believe that these two genes affect the transformation of atypical endometrial hyperplasia to endometrial cancer by influencing macrophage M0. In conclusion, we believe that these key genes can serve as therapeutic targets for endometrial cancer. We have constructed a new endometrial cancer risk prognosis model and column chart based on these key genes, which can be used to identify prognostic features of endometrial cancer patients. This provides a reliable direction for the future treatment of cervical cancer.